ЯДРОСИДА БЕССЕЛЬ ФУНКЦИЯСИ ҚАТНАШГАН ЎРАМСИЗ ОПЕРАТОРЛАР ВА УЛАРНИНГ ХОССАЛАРИ (Scientific journal of the Fergana State University, 2023)
In the paper two packing integral operators which are including Bessel functions in the kernel and their compositional features are investigated.